2005
DOI: 10.1111/j.1365-2966.2005.09303.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatially intermittent fields in photospheric magnetoconvection

Abstract: Motivated by recent high‐resolution observations of the solar surface, we investigate the problem of non‐linear magnetoconvection in a three‐dimensional compressible layer. We present results from a set of numerical simulations which model the situation in which there is a weak imposed magnetic field. This weak‐field regime is characterized by vigorous granular convection and spatially intermittent magnetic field structures. When the imposed field is very weak, magnetic flux tends to accumulate at the edges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
(53 reference statements)
0
29
0
Order By: Relevance
“…In the opposite limit Living Reviews in Solar Physics http://www.livingreviews.org/lrsp-2010-2 of a strong mean field, they found that the dominant scales of turbulent convection are tightly constrained and reduced by magnetic tension. On this topic, we also mention the work of Bushby and Houghton (2005), Bushby et al (2008) and Stein and Nordlund (2006), who investigated the formation process of magnetic ribbons and point-like flux concentrations using mesoscale simulations (accommodating for just a few granules). The first group followed the idealised approach of simulations of three-dimensional compressible magnetoconvection in weak field regimes and the second group a realistic approach, starting their simulation with a uniform horizontal magnetic field.…”
Section: Local Mhd Cartesian Simulationsmentioning
confidence: 99%
“…In the opposite limit Living Reviews in Solar Physics http://www.livingreviews.org/lrsp-2010-2 of a strong mean field, they found that the dominant scales of turbulent convection are tightly constrained and reduced by magnetic tension. On this topic, we also mention the work of Bushby and Houghton (2005), Bushby et al (2008) and Stein and Nordlund (2006), who investigated the formation process of magnetic ribbons and point-like flux concentrations using mesoscale simulations (accommodating for just a few granules). The first group followed the idealised approach of simulations of three-dimensional compressible magnetoconvection in weak field regimes and the second group a realistic approach, starting their simulation with a uniform horizontal magnetic field.…”
Section: Local Mhd Cartesian Simulationsmentioning
confidence: 99%
“…In this context, investigation of fractal and multifractal properties of photospheric magnetic features provide important information about the physical properties of convective plasma (Balke et al 1993;Tao et al 1995;Nesme-Ribes et al 1996), of the magnetic field (Stenflo & Holzreuter 2002;Pietarila Graham et al 2009) and about the physical processes that govern their interaction (Lawrence et al 1995(Lawrence et al , 1999Bushby & Houghton 2005;Crouch et al 2007). Studies carried out on short temporal ranges (hours-days), have showed that fractal and multifractal properties vary with the evolution of the photospheric magnetic field of the regions analyzed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Two complementary approaches using numerical simulations have both contributed toward understanding convection. One uses simplified physics to explore the basic properties of convection and its parameter space variations (e.g., Hurlburt & Toomre 1988;Cattaneo et al 1991;Nordlund et al 1992;Hurlburt et al 1996Hurlburt et al , 2002Brummell et al 1998;Weiss et al 1996;Tao et al 1998;Tobias et al 1998Tobias et al , 2001Porter & Woodward 2000;Thelen & Cattaneo 2000;Emonet & Cattaneo 2001;Cattaneo et al 2003;Cline et al 2003;Brun et al 2004;Bushby & Houghton 2005). The other uses realistic solar physics to enable quantitative comparisons with solar observations and explore physical processes in the solar convection zone (e.g., Nordlund 1985;Freytag et al 1996;Stein & Nordlund 1998, 2001Rosenthal et al 1999;Steiner et al 1998;Asplund et al 2000;Leka & Steiner 2001;Keller et al 2004;Carlsson et al 2004;Vögler et al 2005;Khomenko et al 2005).…”
Section: Introductionmentioning
confidence: 99%